The Effectiveness of Ion Tangkel Media Based on Cooperative Learning Models in Increasing Motivation and Understanding of Mathematics Concepts for Grade 6 Students at SDN 9 Taliwang - Mirsafa, Ludia; Suparman, Suparman; Junaidi, Junaidi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aims to find out the effectiveness of the ion tank media on cooperative learning models and find out what factors influence the effectiveness of ion tank media on cooperative learning models in increasing students' motivation and understanding of concepts. The research method used is an experiment used to determine students' motivation and understanding of concepts after the implementation of cooperative learning model-based ion tank media. The experimental method design used is a group Pretest-Posttest Design. The data collection procedures used include student responses and documentation. Data analysis used includes analysis of student motivation, concept understanding tests, and analysis of student responses. The results of research using six indicators obtained an average value of 81 and were in the effective category. The results of the concept mastery test show an increase from the pretest, with an average score of 54 and the posttest, with an average score of 85. This data shows that students' concept mastery is in the complete category according to the KKM ≥ 70. The results of student responses using cooperative learning model-based ion learning media can increase students' learning motivation and understanding of concepts. The conclusion obtained is that the ion tank media based on the cooperative learning model is effective in increasing students' motivation and understanding of concepts. The role of teachers, cooperative learning models and interactive learning media are factors that influence the effectiveness of increasing motivation and understanding of concepts for grade 6 students at SDN 9 Taliwang.